Efficacy and safety of extracorporeal membrane oxygenation for high-risk pulmonary embolism: A systematic review and meta-analysis. (October 2020) - Pozzi, Matteo; Metge, Augustin; Martelin, Anthony; Giroudon, Caroline; Lanier Demma, Justine; Koffel, Catherine; Fornier, William; Chiari, Pascal; Fellahi, Jean Luc; Obadia, Jean Francois; Armoiry, Xavier
High-risk pulmonary embolism (PE) requires hemodynamic and respiratory support along with reperfusion strategies. Recently updated European guidelines assign a low class of recommendation to extracorporeal membrane oxygenation (ECMO) for high-risk PE. This systematic review assessed clinical outcomes after ECMO in high-risk PE. We searched electronic databases including PubMed, Embase and Web of Science from January 2000 to April 2020. Efficacy outcomes included in-hospital survival with good neurological outcome and survival at follow-up. Safety outcomes included lower limb ischemia and hemorrhagic and ischemic stroke. Where possible (absence of high heterogeneity), meta-analyses of outcomes were undertaken using a random-effects model. We included 16 uncontrolled case-series (533 participants). In-hospital survival with good neurological outcome ranged between 50% and 95% while overall survival at follow-up ranged from 35% to 95%, both with a major degree of heterogeneity (I 2 > 70%). The prevalence of lower limb ischemia was 8% (95% CI 3% to 15%). The prevalence of stroke (either hemorrhagic or ischemic) was 11% (95% CI 3% to 23%), with notable heterogeneity (I² = 63.35%). Based on currently available literature, it is not possible to draw definite conclusions on the usefulness of ECMO for high-risk PE. Prospective, multicenter, large-scale studies or nationwide registries are needed to best define the role of ECMO for high-risk PE.PROSPERO registration ID: CRD42019136282 .